2019
DOI: 10.1037/adb0000485
|View full text |Cite
|
Sign up to set email alerts
|

Does self-efficacy moderate the effect of gambling advertising on problem gambling behaviors?

Abstract: Problem gambling causes significant harm to individuals and society. Financial losses from gambling in Australia exceed those anywhere else in the world. Problem gamblers are overrepresented among substance users and rural and remote Australians. Limited research exists on the impact of gambling advertising on problem gambling among those seeking substance use treatment, in rural/remote areas, and protective factors that may guard against these impacts. This study examined whether self-efficacy to control gamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Thus, in our study, as gambling self-efficacy increases, the effect of perceived gambling availability in gambling behavior decreases and even disappears among those adolescents who perceive high self-efficacy to refuse gambling. In a similar vein, a recent cross-sectional study (Quinn et al, 2019) found that gambling self-efficacy is a protective factor against environmental cues such as gambling advertising.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, in our study, as gambling self-efficacy increases, the effect of perceived gambling availability in gambling behavior decreases and even disappears among those adolescents who perceive high self-efficacy to refuse gambling. In a similar vein, a recent cross-sectional study (Quinn et al, 2019) found that gambling self-efficacy is a protective factor against environmental cues such as gambling advertising.…”
Section: Discussionmentioning
confidence: 86%
“…Consistently with this postulates, self-efficacy has shown to moderate the impact of environmental factors on problem gambling. For example, Quinn et al (2019) found that the impact of gambling advertising on problem gambling was lower among individuals with high selfefficacy to control gambling in comparison with those with low self-efficacy. Therefore, it could be expected that gambling self-efficacy ameliorates the impact of perceived gambling availability on adolescent gambling behavior.…”
mentioning
confidence: 99%
“…For example, placing GameSense RG resources in clearly visible locations in land-based casinos might help to enhance awareness of what educational or help resources are available, which in turn could increase engagement for those at risk or who might want to take proactive steps to gamble in healthier ways. Such an approach might also reduce inattention blindness to these GameSense resources, while empowering patrons with tools to help them manage their gambling behavior by building self-efficacy (see Quinn et al, 2019).…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…However, they thought a stigma existed for those gamblers asking for help. According to Quinn et al (2019) , the global gambling market is expanding and expected to reach $635 billion by 2022, largely because of the proliferation of smart devices delivering gambling products. According to statistical data taken from Gross Gambling Yield ( Lange, 2020 ), in Great Britain, the gambling industry increased from roughly 8.4 billion British pounds in 2011 to approximately 14.4 billion in 2018.…”
Section: Introductionmentioning
confidence: 99%